Verbal Irony as a Communicative Mode of Persuasion - Neshkovska, Silvana; Trajkova, Zorica (London College of United Knowledge Press, 2018)
The general pervasiveness of politics in modern society renders political discourse susceptible to analysis by many different profiles of researchers, especially linguists. This particular paper attempts to shed light on the usage of verbal irony in political discourse. The premise we put forward here is that politicians in their political speeches purposefully employ irony in order to enhance the persuasiveness of their speech. Moreover, we believe that the enhancement of persuasiveness is in a direct correlation with the pragmatic functions of verbal irony. To put it differently, 'seasoning' political speeches with ironic statements which evoke either humor; or express mild ridicule, or harsh criticism at the expense of the political opponent, is what makes them truly persuasive. The corpus compiled for the purposes of this research comprises political speeches delivered by American politicians in the course of the 2016 U.S. presidential race. The results obtained primarily confirm the relatively high incidence of verbal irony in political speeches; then, they also point to the relatively high degree of persuasion attached to irony in general and its association mainly with expressing mild ridicule and harsh criticism.
Keywords: political discourse, verbal irony, meta-discourse markers